CROSS-BORDER TOURISM AND LOCAL DEVELOPMENT: POTENTIALITIES ON THE COSTA RICA-NICARAGUA BORDER - Barrantes Ortega, José Andrés; Rámirez Brenes, Juan Carlos (Geo UERJ, 2019)
This document is the product of a research process that has been done at Universidad Nacional de Costa Rica, Sede Regional Chorotega, within the framework of the Mesoamerican Border Studies Program, with the purpose of understanding the social, economic and cultural dynamics border region of Nicaragua and Costa Rica, this as a starting point to be able to propose and implement models to improve the development of the communities located in this border area, through the activation of local economies.The objective of this document is to present an analysis of the phenomenon of cross-border tourism in the Costa Rica-Nicaragua dyad and its link with the local development of border communities.